Benign Brenner’s tumor of ovary: a case report with review of literature - Hota, Basanta Manjari; Movva, Naimisha; Indu, Mudragada Lakshmi; Dharani, Yalamaddi Ooha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Brenner’s tumor of the ovary is a rare neoplasia with an incidence of 02-03% of all ovarian tumors. Its origin is controversial; the new hypothesis describes it as transitional cell metaplasia of Walthard cell nests embedded in the ovary. The world health organization has classified it into benign, borderline, and malignant varieties, with incidences of 95%, <5%, and <2%, respectively. Benign Brenner’s tumor (BBT) is usually <2 cm in size, unilateral, solid, grayish white, well-circumscribed, rubbery to firm nodule, arising from ovarian cortex and resembling fibroma or thecoma of ovary. The average age of patients is 50 years. Diagnosis of the pathology is challenging as it does not have a specific clinical presentation or investigatory findings, and is usually diagnosed incidentally on histological examination of the ovary resected with other genital organs. Microscopy of the tumor shows a fibro-epithelial solid mass consisting of transitional epithelial cell nests surrounded by dense fibrous tissue. No further treatment is required in benign cases, whereas chemotherapy with or without radiotherapy and follow-up is needed in borderline and malignant cases. A case of unilateral BBT of the ovary in a 42-year-old parous lady was diagnosed in this institution, who had undergone total abdominal hysterectomy with bilateral salpingo-oophorectomy for fibroid uterus with abnormal uterine bleeding (AUB) and severe anemia. The presentation aims to report this rare pathology of Brenner’s tumor without a specific clinical presentation, diagnosed incidentally on histopathological examination (HPE), and to add to the statistics.